A kind of lithium battery negative electrode binder and preparation method thereof
By using 2-amino-1,1,3-tricyano-1-propylene and 2,4,5-trimethoxy-1-propylene polymer as raw materials for the negative electrode binder of lithium batteries, combined with free radical initiator and emulsifier, the problem of insufficient anti-cold and cold impact performance of lithium batteries in the prior art is solved, and the effect of maintaining good performance in a hot and cold environment is achieved.
Patent Information
- Application Number
- CN202310564278.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-18
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-05-18
AI Technical Summary
The negative electrode adhesive of existing lithium battery is poor in hot and cold impact environments, resulting in a degradation of battery electrical performance.
The polymer obtained by polymerization of 2-amino-1,1,3-tricyano-1-propylene and 2,4,5-trimethoxy-1-propylene benzene is used as the binder raw material, and the polymerization reaction is carried out through the combination of a radical initiator, an emulsifier and water to improve the anti-cold impact performance of the binder.
The adhesive maintains a stable structure during high and low temperature switching, has a small expansion coefficient and good toughness, and can effectively maintain the circulation performance of lithium batteries.
Smart Images

Figure BDA0004236240210000081 
Figure BDA0004236240210000091 
Figure BDA0004236240210000111
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium batteries, and more specifically, to a lithium battery negative electrode binder and a preparation method thereof. Background Art
[0002] The negative electrode of lithium battery is mainly made of negative active ingredient carbon material or non-carbon material, binder and additives, which are rubbed on both sides of copper foil, and then processed by drying, extrusion and other processes. The negative electrode material is the main body of lithium storage in lithium-ion batteries, allowing lithium ions to be embedded and released during charging and discharging. When the lithium battery is charged, the lithium atoms in the positive electrode are ionized into lithium ions and electrons, and the lithium ions move to the negative electrode to synthesize lithium atoms with electrons. During discharge, lithium atoms are ionized from the graphite crystal and the surface of the negative electrode into lithium ions and electrons, and synthesize lithium atoms at the positive electrode. The negative electrode material mainly affects the initial efficiency and cycle performance of the lithium battery. The performance of the negative electrode material also directly affects the performance of the lithium battery. The negative electrode material accounts for about 5-15% of the total cost of the lithium battery.
[0003] If the lithium battery has poor resistance to cold and heat shock, it will seriously limit the use of electric vehicles in cold areas. One of the important factors restricting the resistance to cold and heat shock of lithium batteries is the resistance to cold and heat shock of the negative electrode binder. At present, the resistance to cold and heat shock of some lithium battery negative electrode binders is poor. For example, after being used at low temperatures of -40 to -30°C, and then used in an environment above 0°C, the volume expansion rate is large, resulting in a decrease in battery electrical performance. Therefore, it is of great significance to improve the resistance to cold and heat shock of lithium battery negative electrode binders. Summary of the invention
[0004] In order to improve the problem that some lithium battery negative electrode binders have poor resistance to thermal shock and significantly reduce battery cycle performance, this application proposes a lithium battery negative electrode binder and a preparation method thereof, which can maintain good performance when used in a thermal shock environment. To this end, this application adopts the following technical solution.
[0005] In a first aspect, the present application proposes a lithium battery negative electrode binder and adopts the following technical solution.
[0006] A lithium battery negative electrode binder, wherein the raw materials for preparing the binder include 2-amino-1,1,3-tricyano-1-propylene monomer and 2,4,5-trimethoxy-1-propylene benzene monomer; the binder includes a polymer obtained by polymerizing the 2-amino-1,1,3-tricyano-1-propylene and the 2,4,5-trimethoxy-1-propylene benzene.
[0007] By adopting the above technical scheme, 2-amino-1,1,3-tricyano-1-propylene and 2,4,5-trimethoxy-1-propylene benzene are polymerized to obtain a polymer, and the binder includes the polymer. Due to the presence of polycyano groups, polymethoxyphenyl groups and oxidized amino groups, the polymer chains have certain steric hindrance and are not easy to entangle. The cyano group has a strong electron-withdrawing ability and attracts groups such as methoxy and methyl. The influence of steric hindrance and electron-withdrawing effect allows the polymer chains to maintain a certain distance. The structure can be kept stable during the high and low temperature switching process, and the expansion coefficient is small. When used in a cold and hot shock environment, the binder can maintain good toughness and structural stability. The binder has good affinity for graphite, which is beneficial to the transfer of charge and helps to maintain the cycle performance of the lithium battery.
[0008] As an improvement of the negative electrode binder of the lithium battery, the raw materials for preparing the binder also include a free radical initiator, an emulsifier and a solvent.
[0009] By adopting the above technical scheme, the emulsifier emulsifies and disperses 2-amino-1,1,3-tricyano-1-propene and 2,4,5-trimethoxy-1-propenylbenzene in the solvent, and the free radical initiator initiates the polymerization reaction of the two monomers to obtain a liquid polymer that is easy to maintain viscosity and preservation.
[0010] As an improvement of the negative electrode binder of the lithium battery, the free radical initiator is selected from one or more of dihexadecyl peroxydicarbonate, ditetradecyl peroxydicarbonate, bis(4-tert-butylcyclohexyl) peroxydicarbonate and di-(2-ethylhexyl) peroxydicarbonate.
[0011] By adopting the above technical scheme and using the binders prepared by these initiators, the obtained polymer has less side chains, suitable viscosity, and good resistance to thermal shock.
[0012] As an improvement of the negative electrode binder of the lithium battery, the emulsifier is selected from one or more of monoethanolamine borate, diethanolamine borate and triethanolamine borate, and the solvent is water.
[0013] By adopting the above technical scheme, these emulsifiers have strong fusion properties for 2-amino-1,1,3-tricyano-1-propylene and 2,4,5-trimethoxy-1-propylene benzene, and these emulsifiers have high solubility in water, so that 2-amino-1,1,3-tricyano-1-propylene and 2,4,5-trimethoxy-1-propylene benzene have good dispersion effects in water, promote the stable progress of the polymerization reaction, and the generated polymer has good linearity, few branches, suitable viscosity, and good resistance to cold and hot shocks. The polymer prepared with water as the solvent is dispersed in water, and the evaporation rate of water is slower than that of general organic solvents, so that the binder has sufficient condensation time for the manufacture of the negative electrode process, which is convenient for operation. When the battery is made, the water volatilized by the negative electrode material is not easy to support combustion compared with organic solvents, and is safer.
[0014] As an improvement of the negative electrode binder of the lithium battery, some raw materials for preparing the binder and their amounts are, by mass: 40 to 60 parts of the 2-amino-1,1,3-tricyano-1-propylene, 40 to 60 parts of the 2,4,5-trimethoxy-1-propylene benzene, 0.2 to 1 parts of the free radical initiator and 1 to 5 parts of the emulsifier.
[0015] By adopting the above technical scheme, each raw material reacts more fully, the utilization rate of each component is high, the polymerization degree of the generated polymer is more uniform, and it has better resistance to cold and heat shock.
[0016] As an improvement of the negative electrode binder of the lithium battery, some raw materials for preparing the binder and their usage are: 50 parts of the 2-amino-1,1,3-tricyano-1-propylene, 50 parts of the 2,4,5-trimethoxy-1-propylene benzene, 0.5 parts of the free radical initiator and 3 parts of the emulsifier.
[0017] By adopting the above technical solution, all raw materials react fully, the generated polymer has uniform polymerization degree and good resistance to cold and heat shock.
[0018] In a second aspect, the present application also proposes a method for preparing a negative electrode binder for a lithium battery, and adopts the following technical solution.
[0019] A method for preparing the negative electrode binder for a lithium battery as described above, the preparation method comprising mixing the 2-amino-1,1,3-tricyano-1-propylene and the 2,4,5-trimethoxy-1-propylene benzene, a free radical initiator, an emulsifier and water, heating to 60-80° C., and performing a polymerization reaction for 10-20 hours to obtain the binder.
[0020] By adopting the above technical scheme, at 60-80°C, the emulsifier evenly disperses 2-amino-1,1,3-tricyano-1-propene and 2,4,5-trimethoxy-1-propenylbenzene in water, and the free radical initiator supplies free radicals and initiates the polymerization of the monomers. After 10-20 hours of polymerization reaction, the conversion rate of the monomers into polymers reaches 60-95%, which is a relatively sufficient reaction. The obtained adhesive has good resistance to cold and hot shocks.
[0021] As an improvement to the preparation method of the negative electrode binder of the lithium battery, difluorobenzonitrile is added when the 2-amino-1,1,3-tricyano-1-propene and the 2,4,5-trimethoxy-1-propenylbenzene, the free radical initiator, the emulsifier and water are mixed.
[0022] By adopting the above technical solution, difluorobenzonitrile contains cyano, fluoro and phenyl groups, and has a certain repulsion to 2-amino-1,1,3-tricyano-1-propylene, 2,4,5-trimethoxy-1-propylene benzene and polymer chains, thereby further improving the dispersion of 2-amino-1,1,3-tricyano-1-propylene and 2,4,5-trimethoxy-1-propylene benzene in water, improving the reaction rate, and difluorobenzonitrile also improves the dispersion of the generated polymer in water, further reduces the entanglement rate of the polymer, and improves the cold and hot shock resistance of the binder. The difluorobenzonitrile can be 2,3-difluorobenzonitrile, 2,4-difluorobenzonitrile, 3,4-difluorobenzonitrile, 2,5-difluorobenzonitrile or 2,6-difluorobenzonitrile.
[0023] As an improvement to the preparation method of the negative electrode binder for lithium batteries, when preparing the binder, the amounts of the components used are respectively: 40 to 60 parts of the 2-amino-1,1,3-tricyano-1-propylene, 40 to 60 parts of the 2,4,5-trimethoxy-1-propylene benzene, 0.2 to 1 part of a free radical initiator, 1 to 5 parts of an emulsifier, 100 to 150 parts of water, and 1 to 2 parts of difluorobenzonitrile, by mass.
[0024] By adopting the above technical scheme, an appropriate amount of difluorobenzonitrile improves the dispersion of 2-amino-1,1,3-tricyano-1-propene and 2,4,5-trimethoxy-1-propenylbenzene in water and increases the reaction rate. Difluorobenzonitrile also improves the dispersion of the generated polymer in water and reduces the entanglement rate of the polymer, thereby improving the cold and hot shock resistance of the adhesive.
[0025] As an improvement to the preparation method of the negative electrode binder of the lithium battery, copper acetate is added when the 2-amino-1,1,3-tricyano-1-propylene and the 2,4,5-trimethoxy-1-propylene benzene, the free radical initiator, the emulsifier and water are mixed.
[0026] By adopting the above technical solution, the mass ratio of copper acetate to 2-amino-1,1,3-tricyano-1-propylene can be (2-4):(40-60), and copper acetate can enhance the charge transfer effect between the binder and the copper foil.
[0027] In summary, the lithium battery negative electrode binder and its preparation method of the present application have the following beneficial effects: a binder is obtained by polymerizing 2-amino-1,1,3-tricyano-1-propylene and 2,4,5-trimethoxy-1-propylene benzene. Due to the presence of polycyano, polymethoxyphenyl and oxidized amino groups, the polymer chains have certain steric hindrance and are not easy to entangle. The cyano group has a strong electron-withdrawing ability, attracting groups such as methoxy and methyl. The influence of steric hindrance and electron-withdrawing effect keeps a certain distance between the polymer chains, and the structure can be kept stable during the high and low temperature switching process, and the expansion coefficient is small. For example, after being used at a low temperature of -40 to -30°C, it is used again in an environment above 0°C. The binder can maintain good toughness and structural stability, and is resistant to cold and hot shocks. In addition, the binder has a good affinity for graphite, which is conducive to the transfer of charge and helps to maintain the cycle performance of the lithium battery. DETAILED DESCRIPTION
[0028] The following examples are used to specifically describe the lithium battery negative electrode binder and its preparation method of the present application. The following parts of each component are by mass.
[0029] Example 1
[0030] This embodiment prepares a lithium battery negative electrode binder, and the preparation method is as follows.
[0031] Take 50 parts of 2-amino-1,1,3-tricyano-1-propene, 50 parts of 2,4,5-trimethoxy-1-propenylbenzene, 0.5 parts of free radical initiator, 3 parts of emulsifier, and 125 parts of water, mix them evenly to form an emulsion, heat it to 70°C, and perform polymerization reaction for 15 hours to obtain a binder.
[0032] The free radical initiator is dihexadecyl peroxydicarbonate, and the emulsifier is monoethanolamine borate.
[0033] Example 2
[0034] This embodiment prepares a lithium battery negative electrode binder, which is different from Embodiment 1 in that the raw material ratio is different. The preparation method is as follows.
[0035] Take 40 parts of 2-amino-1,1,3-tricyano-1-propene, 60 parts of 2,4,5-trimethoxy-1-propenylbenzene, 0.2 parts of free radical initiator, 5 parts of emulsifier, and 100 parts of water, mix them evenly to form an emulsion, heat it to 70°C, and perform polymerization reaction for 15 hours to obtain a binder.
[0036] The free radical initiator is dihexadecyl peroxydicarbonate, and the emulsifier is monoethanolamine borate.
[0037] Example 3
[0038] This embodiment prepares a lithium battery negative electrode binder, which is different from Embodiment 1 in that the raw material ratio is different. The preparation method is as follows.
[0039] Take 60 parts of 2-amino-1,1,3-tricyano-1-propene, 40 parts of 2,4,5-trimethoxy-1-propenylbenzene, 1 part of a free radical initiator, 1 part of an emulsifier, and 150 parts of water, mix them evenly to form an emulsion, heat it to 70°C, and perform a polymerization reaction for 15 hours to obtain a binder.
[0040] The free radical initiator is dihexadecyl peroxydicarbonate, and the emulsifier is monoethanolamine borate.
[0041] Example 4
[0042] This embodiment prepares a lithium battery negative electrode binder, which is different from embodiment 1 in polymerization temperature and time. The preparation method is as follows.
[0043] Take 50 parts of 2-amino-1,1,3-tricyano-1-propene, 50 parts of 2,4,5-trimethoxy-1-propenylbenzene, 0.5 parts of free radical initiator, 3 parts of emulsifier, and 125 parts of water, mix them evenly to form an emulsion, heat it to 60°C, and perform polymerization reaction for 10 hours to obtain a binder.
[0044] The free radical initiator is dihexadecyl peroxydicarbonate, and the emulsifier is monoethanolamine borate.
[0045] Example 5
[0046] This embodiment prepares a lithium battery negative electrode binder, which is different from embodiment 1 in polymerization temperature and time. The preparation method is as follows.
[0047] Take 50 parts of 2-amino-1,1,3-tricyano-1-propene, 50 parts of 2,4,5-trimethoxy-1-propenylbenzene, 0.5 parts of free radical initiator, 3 parts of emulsifier, and 125 parts of water, mix them evenly to form an emulsion, heat it to 80°C, and perform polymerization reaction for 20 hours to obtain a binder.
[0048] The free radical initiator is dihexadecyl peroxydicarbonate, and the emulsifier is monoethanolamine borate.
[0049] Example 6
[0050] This embodiment prepares a lithium battery negative electrode binder, which is different from Embodiment 1 in that 2,4-difluorobenzonitrile is further added to the raw materials. The preparation method is as follows.
[0051] Take 50 parts of 2-amino-1,1,3-tricyano-1-propene, 50 parts of 2,4,5-trimethoxy-1-propenylbenzene, 0.5 parts of free radical initiator, 3 parts of emulsifier, 125 parts of water, and 1.5 parts of 2,4-difluorobenzonitrile, mix them evenly to form an emulsion, heat it to 70°C, and carry out polymerization reaction for 15 hours to obtain a binder.
[0052] The free radical initiator is dihexadecyl peroxydicarbonate, and the emulsifier is monoethanolamine borate.
[0053] Example 7
[0054] This embodiment prepares a lithium battery negative electrode binder, which is different from Example 1 in that copper acetate is also added to the raw materials. The preparation method is as follows.
[0055] Take 50 parts of 2-amino-1,1,3-tricyano-1-propene, 50 parts of 2,4,5-trimethoxy-1-propenylbenzene, 0.5 parts of free radical initiator, 3 parts of emulsifier, 125 parts of water, and 3 parts of cupric acetate, mix them evenly to form an emulsion, heat it to 70°C, and carry out polymerization reaction for 15 hours to obtain a binder.
[0056] The free radical initiator is dihexadecyl peroxydicarbonate, and the emulsifier is monoethanolamine borate.
[0057] Example 8
[0058] This embodiment prepares a lithium battery negative electrode binder, which is different from Embodiment 1 in that the free radical initiator is different. The preparation method is as follows.
[0059] Take 50 parts of 2-amino-1,1,3-tricyano-1-propene, 50 parts of 2,4,5-trimethoxy-1-propenylbenzene, 0.5 parts of free radical initiator, 3 parts of emulsifier, and 125 parts of water, mix them evenly to form an emulsion, heat it to 70°C, and perform polymerization reaction for 15 hours to obtain a binder.
[0060] The free radical initiator is ditetradecyl peroxydicarbonate, and the emulsifier is monoethanolamine borate.
[0061] Example 9
[0062] This embodiment prepares a lithium battery negative electrode binder, which is different from Embodiment 1 in that the free radical initiator is different. The preparation method is as follows.
[0063] Take 50 parts of 2-amino-1,1,3-tricyano-1-propene, 50 parts of 2,4,5-trimethoxy-1-propenylbenzene, 0.5 parts of free radical initiator, 3 parts of emulsifier, and 125 parts of water, mix them evenly to form an emulsion, heat it to 70°C, and perform polymerization reaction for 15 hours to obtain a binder.
[0064] Wherein, the free radical initiator is bis(4-tert-butylcyclohexyl)peroxydicarbonate, and the emulsifier is monoethanolamine borate.
[0065] Example 10
[0066] This embodiment prepares a lithium battery negative electrode binder, which is different from Embodiment 1 in that the free radical initiator is different. The preparation method is as follows.
[0067] Take 50 parts of 2-amino-1,1,3-tricyano-1-propene, 50 parts of 2,4,5-trimethoxy-1-propenylbenzene, 0.5 parts of free radical initiator, 3 parts of emulsifier, and 125 parts of water, mix them evenly to form an emulsion, heat it to 70°C, and perform polymerization reaction for 15 hours to obtain a binder.
[0068] Wherein, the free radical initiator is di-(2-ethylhexyl) peroxydicarbonate, and the emulsifier is monoethanolamine borate.
[0069] Embodiment 11
[0070] This embodiment prepares a lithium battery negative electrode binder, which is different from Embodiment 1 in that the emulsifier is different. The preparation method is as follows.
[0071] Take 50 parts of 2-amino-1,1,3-tricyano-1-propene, 50 parts of 2,4,5-trimethoxy-1-propenylbenzene, 0.5 parts of free radical initiator, 3 parts of emulsifier, and 125 parts of water, mix them evenly to form an emulsion, heat it to 70°C, and perform polymerization reaction for 15 hours to obtain a binder.
[0072] The free radical initiator is dihexadecyl peroxydicarbonate, and the emulsifier is diethanolamine borate.
[0073] Example 12
[0074] This embodiment prepares a lithium battery negative electrode binder, which is different from Embodiment 1 in that the emulsifier is different. The preparation method is as follows.
[0075] Take 50 parts of 2-amino-1,1,3-tricyano-1-propene, 50 parts of 2,4,5-trimethoxy-1-propenylbenzene, 0.5 parts of free radical initiator, 3 parts of emulsifier, and 125 parts of water, mix them evenly to form an emulsion, heat it to 70°C, and perform polymerization reaction for 15 hours to obtain a binder.
[0076] The free radical initiator is dihexadecyl peroxydicarbonate, and the emulsifier is triethanolamine borate.
[0077] Comparative Example 1
[0078] This comparative example prepares a lithium battery negative electrode binder, which differs from Example 1 in that a free radical initiator is different. The preparation method is as follows.
[0079] Take 50 parts of 2-amino-1,1,3-tricyano-1-propene, 50 parts of 2,4,5-trimethoxy-1-propenylbenzene, 0.5 parts of free radical initiator, 3 parts of emulsifier, and 125 parts of water, mix them evenly to form an emulsion, heat it to 70°C, and perform polymerization reaction for 15 hours to obtain a binder.
[0080] Wherein, the free radical initiator is benzoyl peroxide, and the emulsifier is monoethanolamine borate.
[0081] Comparative Example 2
[0082] This comparative example prepares a lithium battery negative electrode binder, which differs from Example 1 in that a free radical initiator is different. The preparation method is as follows.
[0083] Take 50 parts of 2-amino-1,1,3-tricyano-1-propene, 50 parts of 2,4,5-trimethoxy-1-propenylbenzene, 0.5 parts of free radical initiator, 3 parts of emulsifier, and 125 parts of water, mix them evenly to form an emulsion, heat it to 70°C, and perform polymerization reaction for 15 hours to obtain a binder.
[0084] Wherein, the free radical initiator is potassium persulfate, and the emulsifier is monoethanolamine borate.
[0085] Comparative Example 3
[0086] This comparative example prepares a lithium battery negative electrode binder, which differs from Example 1 in that the emulsifier is different. The preparation method is as follows.
[0087] Take 50 parts of 2-amino-1,1,3-tricyano-1-propene, 50 parts of 2,4,5-trimethoxy-1-propenylbenzene, 0.5 parts of free radical initiator, 3 parts of emulsifier, and 125 parts of water, mix them evenly to form an emulsion, heat it to 70°C, and perform polymerization reaction for 15 hours to obtain a binder.
[0088] Wherein, the free radical initiator is dihexadecyl peroxydicarbonate, and the emulsifier is sodium lauryl sulfate.
[0089] Comparative Example 4
[0090] This comparative example prepares a lithium battery negative electrode binder, which differs from Example 1 in that the emulsifier is different. The preparation method is as follows.
[0091] Take 50 parts of 2-amino-1,1,3-tricyano-1-propene, 50 parts of 2,4,5-trimethoxy-1-propenylbenzene, 0.5 parts of free radical initiator, 3 parts of emulsifier, and 125 parts of water, mix them evenly to form an emulsion, heat it to 70°C, and perform polymerization reaction for 15 hours to obtain a binder.
[0092] Wherein, the free radical initiator is dihexadecyl peroxydicarbonate, and the emulsifier is polyoxyethylene ether.
[0093] Comparative Example 5
[0094] This comparative example prepares a lithium battery negative electrode binder, which differs from Example 1 in that the raw material ratio is different. The preparation method is as follows.
[0095] Take 25 parts of 2-amino-1,1,3-tricyano-1-propene, 75 parts of 2,4,5-trimethoxy-1-propenylbenzene, 0.5 parts of free radical initiator, 3 parts of emulsifier, and 125 parts of water, mix them evenly to form an emulsion, heat it to 70°C, and perform polymerization reaction for 15 hours to obtain a binder.
[0096] The free radical initiator is dihexadecyl peroxydicarbonate, and the emulsifier is monoethanolamine borate.
[0097] Comparative Example 6
[0098] This comparative example prepares a lithium battery negative electrode binder, which differs from Example 1 in that the raw material ratio is different. The preparation method is as follows.
[0099] Take 50 parts of 2-amino-1,1,3-tricyano-1-propene, 50 parts of 2,4,5-trimethoxy-1-propenylbenzene, 5 parts of free radical initiator, 0.2 parts of emulsifier, and 125 parts of water, mix them evenly to form an emulsion, heat it to 70°C, and perform polymerization reaction for 15 hours to obtain a binder.
[0100] The free radical initiator is dihexadecyl peroxydicarbonate, and the emulsifier is monoethanolamine borate.
[0101] Test Example 1
[0102] Preparation of negative electrode samples: Take 3g of the binder prepared in Examples 1-12 and Comparative Examples 1-6, mix 6g of graphite powder in each, and then apply them on both sides of 18 identical copper foils, with the same coating thickness on both sides, heat to 160°C for 40min to solidify the binder, and cool at room temperature to obtain 18 negative electrode samples. Then the 18 negative electrode samples were subjected to a hot and cold shock test. The hot and cold shock test conditions were to keep at -40°C for 1h, then heat to 40°C within 30min and continue for 1h, and repeat the test for 14 days. During the hot and cold shock process, the changes of each negative electrode sample were observed every 24h. The results showed that the negative electrode sample prepared by the product of Comparative Example 3 showed a slight whitening phenomenon on the 12th day, and the negative electrode sample prepared by the product of Comparative Example 4 showed a slight whitening phenomenon on the 13th day. No obvious abnormality was observed in the remaining samples. The results show that the adhesive prepared by using sodium dodecyl sulfate or polyoxyethylene ether as emulsifier has weaker resistance to cold and hot shock than that prepared by using monoethanolamine borate, diethanolamine borate or triethanolamine borate as emulsifier.
[0103] The thickness of 18 negative electrode samples was tested before the hot and cold shock test, and the thickness of 18 negative electrode samples was tested again after the test. The thickness change rate of each negative electrode sample was calculated = (thickness after test - thickness before test) / thickness before test * 100%. The results are shown in Table 1.
[0104] Table 1 Abnormal changes of each negative electrode sample during hot and cold shock
[0105]
[0106]
[0107] As can be seen from Table 1, the thickness growth rate of Examples 1-12 is relatively small, while the thickness growth rate of Comparative Examples 1-6 is relatively large. The thickness growth rate of Example 4 is slightly larger, which is due to the fact that its polymerization conditions are heating to 60°C and carrying out the polymerization reaction for 10 hours, which are both relatively small, the monomer conversion rate is relatively low, the polymer molecular weight and concentration are relatively low, and the adhesion to graphite is not large enough.
[0108] Comparative Example 1 uses benzoyl peroxide as a free radical initiator, and Comparative Example 2 uses potassium persulfate as a free radical initiator. The prepared adhesives have a lower thermal shock resistance than the adhesives prepared by using carbonates such as dihexadecyl peroxydicarbonate, ditetradecyl peroxydicarbonate, bis(4-tert-butylcyclohexyl) peroxydicarbonate, and di-(2-ethylhexyl) peroxydicarbonate as free radical initiators.
[0109] Comparative Example 3 uses sodium dodecyl sulfate as an emulsifier, and Comparative Example 4 uses polyoxyethylene ether as an emulsifier. The emulsification effects of 2-amino-1,1,3-tricyano-1-propene and 2,4,5-trimethoxy-1-propenylbenzene in water are not as good as monoethanolamine borate, diethanolamine borate and triethanolamine borate. The resulting polymers have slightly poorer flexibility, slightly more side chains, greater viscosity, and poor resistance to cold and hot shocks.
[0110] Compared with Example 1, Comparative Example 5 changes the ratio of the two monomers, resulting in a larger amount of one of the monomers, which may cause addition polymerization and more branching, resulting in a weaker thermal shock resistance of the generated adhesive.
[0111] Compared with Example 1, Comparative Example 6 changes the ratio of the auxiliary agents. On the one hand, there is too much free radical initiator, which aggravates the reaction. On the other hand, there is too little emulsifier, which weakens the dispersibility of the monomer. These two factors cause the raw materials to react violently locally, and the generated polymer has many side chains, resulting in unbalanced results, causing the generated adhesive to have poor resistance to cold and hot shocks.
[0112] Test Example 2
[0113] Take 18 negative electrode samples prepared in the same way as in Test Example 1 for flexibility test. Wrap a pair of driving shafts and driven shafts with adhesive tape as a transmission tape, with the adhesive side of the tape facing outward, and stick one side of the 18 negative electrode samples on the tape. The driving shaft has a diameter of 25 mm, the driven shaft has a diameter of 3 mm, and the center distance between the driving shaft and the driven shaft is 50 mm. Start the driving shaft at a speed of 20 r / min, rotate the driving shaft 100 times, and test the slag drop rate of each negative electrode sample. See Table 2.
[0114] Table 2 Slag drop rate (flexibility) test of each negative electrode sample
[0115] Slag rate Example 1 15.6% Example 2 18.4% Example 3 17.2% Example 4 19.3% Example 5 20.5% Example 6 16.7% Example 7 19.2% Example 8 22.8% Example 9 20.9% Example 10 17.1% Embodiment 11 16.5% Example 12 14.9% Comparative Example 1 29.7% Comparative Example 2 25.4% Comparative Example 3 28.2% Comparative Example 4 30.6% Comparative Example 5 35.1% Comparative Example 6 27.8%
[0116] The results in Table 2 show that the flexibility of the negative electrode samples made with the binders prepared in Examples 1-12 is better than the flexibility of the negative electrode samples made with the binders prepared in Comparative Examples 1-6.
[0117] Test Example 3
[0118] Preparation of negative electrode samples: Take 3g of each binder prepared in Examples 1-12 and Comparative Examples 1-6, mix 6g of graphite powder in each, and then apply them on both sides of 18 identical copper foils respectively, with the same coating thickness on both sides, heat to 160°C for 40min to solidify the binder, cool at room temperature, and obtain 18 negative electrode samples. Perform resistivity tests on the 18 negative electrode samples. At the same room temperature, test the resistivity of the negative electrode samples made of the binders prepared in Examples 1-12 and Comparative Examples 1-6. Use a digital resistance tester to apply the same voltage on both sides of the negative electrode to test the resistivity between the two sides of the negative electrode. Perform the hot and cold shock test of the 18 negative electrode samples as in Test Example 1 for 14 days, and then test the resistivity again. The results are shown in Table 3.
[0119] Table 3 Resistivity of each negative electrode sample before and after thermal shock
[0120]
[0121] It can be seen from Table 3 that the resistivity of the negative electrode prepared by the binder prepared in Examples 1-12 is smaller than that of Comparative Examples 1-6, and the change rate of the resistivity of the negative electrode prepared by the binder prepared in Examples 1-12 after thermal shock is also smaller, while the change rate of the resistivity of the negative electrode prepared by the binder prepared in Comparative Examples 1-6 after thermal shock is larger. This indicates that the binder prepared by the embodiment scheme has a better conductive effect and better thermal shock resistance.
[0122] From the above, it can be seen that the lithium battery negative electrode binder and its preparation method of the present application are obtained by polymerizing 2-amino-1,1,3-tricyano-1-propylene and 2,4,5-trimethoxy-1-propylene benzene to obtain a binder with a small expansion coefficient, resistance to cold and hot shocks, and good toughness and structural stability. The contact resistance between the binder and the current collector is small, and it can withstand cold and hot shocks and maintain a low resistivity.
[0123] The above are only preferred implementation modes of the present application. The protection scope of the present application is not limited to the above embodiments. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications without departing from the principles of the present application should also be regarded as falling within the protection scope of the present application.
Claims
1. A lithium battery negative electrode binder, characterized in that: The raw materials for preparing the binder include 2-amino-1,1,3-tricyano-1-propylene and 2,4,5-trimethoxy-1-propylene benzene; the binder includes a product of polymerization of the 2-amino-1,1,3-tricyano-1-propylene and the 2,4,5-trimethoxy-1-propylene benzene; The raw materials for preparing the binder also include free radical initiator, emulsifier and solvent; The free radical initiator is selected from one or more of dihexadecyl peroxydicarbonate, ditetradecyl peroxydicarbonate, bis(4-tert-butylcyclohexyl) peroxydicarbonate and di-(2-ethylhexyl) peroxydicarbonate; The emulsifier is selected from one or more of monoethanolamine borate, diethanolamine borate and triethanolamine borate, and the solvent is water; By mass, some raw materials and their amounts for preparing the adhesive are: 40 to 60 parts of the 2-amino-1,1,3-tricyano-1-propylene, 40 to 60 parts of the 2,4,5-trimethoxy-1-propylene benzene, 0.2 to 1 parts of the free radical initiator and 1 to 5 parts of the emulsifier.
2. The negative electrode binder for lithium batteries according to claim 1, characterized in that: By mass, some raw materials for preparing the adhesive and their usage are: 50 parts of the 2-amino-1,1,3-tricyano-1-propylene, 50 parts of the 2,4,5-trimethoxy-1-propylene benzene, 0.5 parts of the free radical initiator and 3 parts of the emulsifier.
3. A method for preparing a negative electrode binder for a lithium battery as claimed in claim 1 or 2, characterized in that: The preparation method comprises mixing the 2-amino-1,1,3-tricyano-1-propylene and the 2,4,5-trimethoxy-1-propylene benzene, a free radical initiator, an emulsifier and water, heating to 60-80° C., and performing a polymerization reaction for 10-20 hours to obtain the binder.
4. The method for preparing a negative electrode binder for a lithium battery according to claim 3, characterized in that: When the 2-amino-1,1,3-tricyano-1-propene and the 2,4,5-trimethoxy-1-propenylbenzene, a free radical initiator, an emulsifier and water are mixed, difluorobenzonitrile is also added.
5. The method for preparing a negative electrode binder for a lithium battery according to claim 4, characterized in that: When preparing the adhesive, the amounts of the components used are: 40-60 parts of the 2-amino-1,1,3-tricyano-1-propene, 40-60 parts of the 2,4,5-trimethoxy-1-propenylbenzene, 0.2-1 parts of a free radical initiator, 1-5 parts of an emulsifier, 100-150 parts of water, and 1-2 parts of difluorobenzonitrile.
6. The method for preparing a negative electrode binder for a lithium battery according to claim 3, characterized in that: When the 2-amino-1,1,3-tricyano-1-propene and the 2,4,5-trimethoxy-1-propenylbenzene, a free radical initiator, an emulsifier and water are mixed, copper acetate is also added.
Citation Information
Patent Citations
Method for producing (E)-2,4,5-trimethoxy-1-propenylbenzene
CN102199077A
Negative pole binder, preparation method therefor and preparation method for negative pole piece
CN108203482A